Antimicrobial activity of silver nanoparticles synthesised by using microbial biosurfactant produced by a newly isolated Bacillus vallismortis MDU6 strain. Issue 9 (17th October 2019) - Das, Moonjit; Borah, Debajit; Patowary, Kaustuvmani; Borah, Mayuri; Khataniar, Ankita; Bhusan Kakoti, Bibhuti
Abstract : Microbial biosurfactants has evolved as green molecules and their chemical diversity has gained momentum in recent time not only in the field of environmental and industrial sectors but also in the pharmaceutical sector. In this study, an effort was made for the biosynthesis of silver nanoparticle (AgNPs) having antimicrobial and non‐cytotoxic activities with the help of microbial biosurfactant extracted from a novel Bacillus vallismortis strain MDU6 (Genbank accession no. MH382951) from petroleum oil logged soil sample in Dibrugarh, Assam. The isolate shows excellent potential for the production of biosurfactant by reducing the surface tension of diesel supplemented medium up to 56.57% only within 5 days. FTIR spectra of the crude biosurfactant show the presence of ʋ CH2 (asymmetric stretching), ʋ CH2 (symmetric stretching), ʋ C=C (stretch), ʋ C−C (stretch), ʋ C−H (bending), ʋ C−O (stretch) and ʋ C−H (bending) functional groups and LC‐MS/MS analysis confirms it as a cyclic lipopeptide which is a mixture of surfactin and iturin. The synthesized AgNPs showed excellent antimicrobial activities against Escherichia coli (ATCC no. 25922), Listeria monocytogenes (ATCC No. BAA‐751), Staphylococcus aureus (ATCC No. 9542) and Bacillus subtilis (ATCC no. 6051) and showed no cytotoxicity against primary mouse liver cell lines.